EFFECT OF CURRENT RATIO, TOTAL ASSET TURNOVER AND NET PROFIT MARGIN AGAINST RETURN ON ASSETS AT PT. ULTRAJAYA MILK INDUSTRY & TRADING period 2010-2019 - Firli Agusetiawan Shavab (Program Studi Manajemen Fakultas Ekonomi Universitas Galuh, 2020)
The research aims to determine the partial and simultaneous influence of current Ratio (CR), Total Asset Turn Over (TATO), and Net Profit Margin (NPM) against Return on Assets (ROA) at PT. Ultra Jaya Milk Industry & Trading Company Tbk. Year 2010-2019. The Data used is sourced from the annual financial report at PT. Ultra Jaya Milk Industry & Trading Company, Tbk in the form of balance sheet and Income Statement report or annual Reprort. After the data is collected, it is analyzed by using classic assumption test model, double Linear regression, determination and hypothesis test. Based on results of analysis of research hypotheses on the level of 95% confidence showed that simultaneously CR, TATO and NPM against ROA have a significant influence on PT. Ultra Jaya Milk Industry & Trading Company Tbk. And in a partial CR it has a negative and insignificant influence on ROA in PT. Ultra Jaya Milk Industry & Trading Company TBK, while TATO and NPM have a positive and significant impact on ROA.